2017
DOI: 10.4269/ajtmh.16-0688
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Potential Sources of Exposure Along the Child Feces Management Pathway: A Cross-Sectional Study Among Urban Slums in Odisha, India

Abstract: Abstract.Child feces represent a particular health risk to children due to increased prevalence of enteric agents and a higher risk of exposure owing to exploratory behaviors of young children. The safe management of such feces presents a significant challenge, not only for the 2.4 billion who lack access to improved sanitation, but also due to unhygienic feces collection and disposal and poor subsequent handwashing practices. We assessed potential sources of fecal exposure by documenting child feces managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Despite the evidence to the contrary, the feces of children are less likely to be safely disposed of in a toilet than those of the general population, and poor disposal of children's feces is drowning the open defecation free (ODF) progress throughout the globe [1][2][3][17][18][19][20][21]. According to the United Nations Child Fund (UNICEF) and the World Bank Global Water Practice's (WSP), over 50% of households with children under age three reported that the feces of their children were unsafely disposed of [3,22].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the evidence to the contrary, the feces of children are less likely to be safely disposed of in a toilet than those of the general population, and poor disposal of children's feces is drowning the open defecation free (ODF) progress throughout the globe [1][2][3][17][18][19][20][21]. According to the United Nations Child Fund (UNICEF) and the World Bank Global Water Practice's (WSP), over 50% of households with children under age three reported that the feces of their children were unsafely disposed of [3,22].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the evidence to the contrary, the feces of children are less likely to be safely disposed of in a toilet than those of the general population, and poor disposal of children feces is drowning the open defecation free (ODF) progress throughout the globe [1,3,[17][18][19][20][21][22][23]. According to the United Nations Child Fund (UNICEF) and the World Bank Global Water Practice's (WSP), over 50 percent of households with children under age three reported that the feces of their children were unsafely disposed of [3,24].…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition, many households with access to sanitation facilities do not dispose of their young children’s feces in the latrine. 24 Poor child feces management (CFM) presents a particular health risk because young children often have the highest incidence of enteric infections 5 and poorly developed immune systems, so their feces likely contain higher quantities of transmissible pathogens. 6 Young children also tend to defecate in areas closer to households, where susceptible children could be exposed, 7 because young children spend large amounts of time on the ground and commonly engage in exploratory behaviors that include putting fingers, fomites, and soil in their mouths.…”
Section: Introductionmentioning
confidence: 99%
“…16–18 There is also evidence that children’s feces are not commonly disposed of in a latrine, with previous studies in Odisha, India, finding that only about a quarter of households with latrines safely disposed of children’s feces into the latrine in rural study areas 19 and in urban slum study areas. 4…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation